Development of an Interactive Multimedia-Based Science Practicum Guide on Dynamic Electricity - Maubuthy, Markus Simeon K.; Supu, Amiruddin; Bani, Marsi D. S.; Sukarjita, I Wayan; Jewaru, Aurelia Astria L.; Tefa, Maria (Experiment: Journal of Science Education, 2025)
This study aims to develop an interactive multimedia-based science practicum guide on dynamic electricity to enhance students' laboratory skills. The research method used in this study was research and development (RD), adapted from both Borg Gall’s and Alessi Trollip’s model. The multimedia product was designed to present the dynamic electricity topic with interactive visualization, equipped with easy-to-use navigation to assist students in conducting experiments. As a manual, the main content includes the practicum objectives, theoretical background, tools and materials, step-by-step procedures with animations, and practice questions with automatic assessment. This practicum guide offers three activities that users can choose from: measuring electric current, measuring voltage difference, and determining the relationship between electric current and voltage difference. The findings indicate that the developed practicum guide is highly feasible as a learning medium for 9th-grade students and effectively enhances their laboratory skills.